VITAMIN C AS AN ADD ON SUPPLEMENTATION TO STANDARD ANTITUBERCULAR TREATMENT IMPROVES SPUTUM SMEAR CONVERSION IN NEWLY DIAGNOSED DRUG SENSITIVE PULMONARY TUBERCULOSIS PATIENTS - Patel, Mrugank; Sinha, Anita; Mistry, Jeenal; Vadgama, Parul; Rathod, Khushbu; Patel, Bhargavi (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: This study was aimed to evaluate the effect of oral supplementation of Vitamin C along with standard anti-tubercular (anti-TB) drugs on the sputum smear conversion in newly diagnosed pulmonary tuberculosis (TB) patients. Methods: This was a prospective, observational study in which 49 newly diagnosed pulmonary TB patients were given oral vitamin C supplementation along with standard anti-TB treatment during the intensive phase (2 months) of the treatment. An examination of the sputum smear at the end of the intensive phase of anti-tubercular treatment was done. At the end of the intensive phase, a comparison was done between the results of the sputum smear examination of the study population and the TB patients of the general population from the same locality who were receiving only standard anti-TB treatment and not add on Vitamin C supplementation. Results: The comparison between the results of the study population (sputum conversion–100%) with those of the general population (sputum conversion–92.47%) shows a significant difference between both populations with p<0.05 (p=0.041). Conclusion: This study showed that Vitamin C supplementation as an add-on therapy to the existing standard anti-TB treatment improves sputum smear conversion and decreases disease activity to a greater extent than routine standard anti-TB treatment alone.